2003
DOI: 10.1590/s1516-31802003000200007
|View full text |Cite
|
Sign up to set email alerts
|

HPV 16 detection in cervical lesions, physical state of viral DNA and changes in p53 gene

Abstract: CONTEXT: Persistent infection with high risk human papillomavirus (HPV) has been linked to cervical carcinoma. Integration of viral DNA into host cell DNA is essential for this cancer development, promoting disruption of the HPV E2 gene, thus leading to unregulated increases in E6 and E7 proteins and inactivating the products of p53 and Rb tumor suppressor genes. OBJECTIVE: To investigate HPV 16 infection in cervical lesions, physical state of viral DNA and p53 gene alterations in a group of women attending a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 14 publications
(11 reference statements)
1
12
0
1
Order By: Relevance
“…Various epidemiological investigations have already shown that periodic convocation of women is essential to conduct a proper follow up, and this helps explain the program's efficiency [24]. We focused on an intermediate-economic-level female population that had good access to health care; in fact, we did not find cancer cases, corroborating the idea that the victims of cervical cancer are poor women, with a low level of education and limited access to medical care [7].…”
Section: Retrospective Analysis Of the Patients Samples (N)supporting
confidence: 70%
See 1 more Smart Citation
“…Various epidemiological investigations have already shown that periodic convocation of women is essential to conduct a proper follow up, and this helps explain the program's efficiency [24]. We focused on an intermediate-economic-level female population that had good access to health care; in fact, we did not find cancer cases, corroborating the idea that the victims of cervical cancer are poor women, with a low level of education and limited access to medical care [7].…”
Section: Retrospective Analysis Of the Patients Samples (N)supporting
confidence: 70%
“…High annual cancer incidences have been reported in Brazil. Nevertheless, there have been few published epidemiological studies concerning the prevalence of HPV DNA in the female genital tract and the natural history of the infection [7]. Vaccine trials against HPV are underway, and one of the problems in vaccine development is to accurately determine which types of HPV to include, since geographical variations in the prevalence of high-risk types have been observed [8].…”
mentioning
confidence: 99%
“…HPV-DNA was investigated by PCR, using the protocol previously established which detects a fragment of 450 base pair (bp) of L1 gene region using consensus primers MY09/11. All positive samples were screened for HPV genotype 16 using a PCR reaction to detect the most common types: 6, 11, 16, 18, 31, 33, and 35. A blood sample was collected for HIV testing: enzyme-linked immunosorbent serologic assay (ELISA; HIV-1 Micro-elisa, Organon Laboratories, Boxtel, Holland) and confirmed by indirect immunofluorescent assay (Fiocruz, Rio de Janeiro).…”
Section: Methodsmentioning
confidence: 99%
“…De acordo com Bosch et al (2002), em estudo de caso controle com amostras provenientes da cérvice uterina é observado a presença de HPV na faixa e 90% a 100%, com o auxílio de técnicas moleculares. No Brasil, estudos similares observaram a presença do HPV entre 73,9% a 95% das amostras (Noronha et al 1999;Cavalcanti et al 2000;Oliveira et al 2003). As variações encontradas nos trabalhos citados e a porcentagem de HPV observada no presente estudo, deve-se a dois fatores: os trabalhos citados correlacionam os resultados do uso de diferentes técnicas moleculares na metodologia como, por exemplo, PCR, RFLP, hibridização in situ e ou captura híbrida I e II.…”
Section: Resultsunclassified